Research on dust and rockburst control technology for coal mining and mathematical correlation - Qingfeng Xu; Shoujian Peng; Jiang Xu; Weimin Cheng; Feng Jiao; Rulin Liu (Scientific Reports)
Abstract As many coal mines in China enter the deep mining stage, underground mining is starting to cause some problems, including dust disasters, rockburst, and coal and gas outburst in enclosed sites. In this study, water injection tests were conducted on coal samples using a coal rock multi-field seepage simulation experimental system under geo-stress conditions. Experimental results demonstrate that, as the cycle period increases, permeability exhibits a gradual increase. Areas with high permeability change rates are predominantly observed at the beginning and end of the cycle. The relationship between permeability and the number of cycles is initially linear during the early and middle cycles. However, beyond 30 cycles, the relationship transitions from linear to nonlinear, indicating an accelerated permeability change after a certain cycle threshold. In conclusion, this study addressed and refined the mathematical relationship between volumetric strain and permeability. The findings of this research have significant implications for the prevention of dust emissions and the mitigation of rockburst disasters in the field.